Creación de un sistema administrativo - contable automatizado para la empresa de lubricantes “los ángeles” en el recinto los ángeles del cantón Buena Fe - Quinga Verdezoto, Hugo Marcelo (2012)
The purpose of this work is to implement a system of control administrative accountant the same one that will allow to maintain modernized the information of the products, to control the revenues and merchandise expenditures, to emit invoices in an automatic way and to obtain costs for product in an easy and quick way. The system of information has been developed using the following tools: Visual Microsoft Studio.Net 2010 and Database SQL Server 2005. After the development of the system, implemented it in the company, through this application the administrator and users responsible for billing and winery may use the program to perform the following processes: To register Client, Suppliers, Products, to create, to modify, to print and to eliminate positions, users, unit of measures, categories, parameters, Movements Billing sales, merchandise entrance, preform, to generate. Report, by means of consultations carried out as they are invoices to get paid, to pay and the clients' conquered invoices, to change their countersign, to carry out revenues of products and office of the same ones to the clients. All who enter the system should log by entering your username and password. In summary this system of control administrative accountant will allow the users of the system to enter, egresses and to control existent products and to verify minimum stock and maximum, to have a bigger control of the existent products to avoid the lack of products and power to generate the sales, in the same way he/she will be able to obtain reports to carry out inventories and to verify the invoices that are required.